The Unemployment Gap as an Alternative Indicator to Detect Macroeconomic Imbalances in the EU (Research Bulletins of the Faculty of Economic Sciences, 2015)
The sharp crisis, the explosion of unemployment rate and the threat of loss solvency in some countries led to the implementation of a number of new initiatives to strengthen the coordination and surveillance of national economic policies in the EU. The main tool for achieving this is the Macroeconomic Imbalance Procedure, which is an important element of preventive detection and possible correction of any imbalances. The table of indicators (Scoreboard), containing 11 indicators of well defined, acceptable thresholds is used for detection of the imbalances. Monitoring labour market, which is an important element to detects imbalances at the macro level way, based on the observation of the unemployment rate, expressed in the form of 3-year moving average. However, such an indicator fulfill the function is not enough for early detection of imbalances. On the contrary, in the years immediately preceding the outbreak of the crisis (2006-2008), this indicator informed about the continuous improvement of the balance of labour markets in the EU countries. This paper presents an alternative indicator to detect imbalances – the unemployment gap, defined as the difference between the actual unemployment rate and the NAIRU. The study leads to the conclusion that the unemployment gap is a significantly better way than     3-years unemployment rate to indicates the presence of any potentially dangerous imbalances. The method for determining the relevance and sustainability of the detected imbalances is a separate issue, which is likely to be the subject of further research. Monitoring labour market imbalances by unemployment gap is an attempt to detect failures at a very early stage of their occurrence and gives   a chance to take the necessary corrective action.
Keywords: policy coordination; macroeconomic imbalances; Scoreboard; crisis management